2017
DOI: 10.1177/1420326x17694476
|View full text |Cite
|
Sign up to set email alerts
|

First- and second-hand smoke dispersion analysis from e-cigarettes using a computer-simulated person with a respiratory tract model

Abstract: The purpose of this study was to investigate, in the human respiratory tract, the flow patterns and adsorption flux (deposition flux) distributions of volatile organic compounds (VOCs) generated by the use of electronic cigarettes (e-cigarettes) through the application of a three-dimensional computational fluid dynamics (CFD) analysis. Two types of human respiratory tract models, which give detailed respiratory tract geometries were reproduced in this study using computed tomography data, for the CFD analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The model has 38 outlet openings for the bronchiole and excluded the nasal cavity region to reduce computational cost. We had confirmed that flow patterns in the respiratory tract did not depend on the existence of the nasal cavity region prior to inhalation exposure analysis using the respiratory tract excluding nasal cavity region 39,55 . The airway model had already been developed based on computer tomography (CT) data extracted from a healthy human male.…”
Section: Methodsmentioning
confidence: 78%
“…The model has 38 outlet openings for the bronchiole and excluded the nasal cavity region to reduce computational cost. We had confirmed that flow patterns in the respiratory tract did not depend on the existence of the nasal cavity region prior to inhalation exposure analysis using the respiratory tract excluding nasal cavity region 39,55 . The airway model had already been developed based on computer tomography (CT) data extracted from a healthy human male.…”
Section: Methodsmentioning
confidence: 78%
“…33 The LRN-AKN model has been widely applied in various types of flow analyses in enclosed spaces and is known for its reasonable prediction accuracy. [33][34][35][36] In order to simulate the inspiratory airflow and particle transport in inter-subject models, a prior estimation of the airflow rates in human is necessary. The inhalation flow rates were considered as a function of metabolic rate, e.g.…”
Section: Governing Equationmentioning
confidence: 99%
“…For example, the concentration of surgical smoke particles from a short-term, high-frequency electrosurgical knife can reach 60,000 -100,000 m -3 in 5 min. Laser scalpels produce approximately twice the concentration of particulate matter in smoke (Imani et al, 2018;Kuga et al, 2018). There are significant differences between superficial and abdominal surgeries, which produce PM2.5 concentrations of 245.7 and 149.4 μg m -3 after 3 -6 s of electrosurgical opening, respectively (Chen et al, 2018;Golda et al, 2019).…”
Section: Airborne Particles As Main Component Of Surgical Smokementioning
confidence: 99%
“…Laser scalpels produce approximately twice the concentration of particulate matter in smoke (Imani et al, 2018;Kuga et al, 2018). There are significant differences between superficial and abdominal surgeries, which produce PM2.5 concentrations of 245.7 and 149.4 μg m -3 after 3 -6 s of electrosurgical opening, respectively (Chen et al, 2018;Golda et al, 2019). However, previous research has not focused on the monitoring and hazard analysis of the particle…”
Section: Airborne Particles As Main Component Of Surgical Smokementioning
confidence: 99%